Socialization of Voting Procedures Elections 2019 In Border Areas In Indonesia Malaysia - Susan Neni Triani; Nindy Citroresmi Prihatiningtyas; Rosmaiyadi Rosmaiyadi; Rien Anitra; Insan Suwanto; Nurul Husna; Dian Mayasari; Mardian Mardian (STKIP Singkawang, 2019)
The purpose of this public service activity is to provide information and knowledge to people in the border areas of the electoral procedure in 2019 which will be held in April 2019. To achieve Reviews These goals, do the